A current perspective on the pathological assessment of FOXL2 in adult‐type granulosa cell tumours of the ovary. Issue 3 (6th November 2013) - Kommoss, Stefan; Gilks, Cyril Blake; Penzel, Roland; Herpel, Esther; Mackenzie, Robertson; Huntsman, David; Schirmacher, Peter; Anglesio, Michael; Schmidt, Dietmar; Kommoss, Friedrich
<x xml:space="preserve">Abstract</x> Aims The diagnosis of adult‐type granulosa cell tumours of the ovary (aGCT) is based on histomorphology aided by immunohistochemical staining for sex cord markers. Recently a single, recurrent somatic point mutation (402C→G) in FOXL2 was described in aGCT. We have investigated the impact of FOXL2 mutation testing in a large cohort of aGCT diagnosed previously by conventional histology and immunohistochemistry. Methods and results Formalin‐fixed, paraffin‐embedded tissue cores from a cohort of 52 aGCT diagnosed previously by expert gynaecopathologists were analysed immunohistologically. FOXL2 mutation status was determined by Sanger sequencing and high‐sensitivity TaqMan allelic discrimination assay. Histomorphology was reassessed by two expert gynaecopathologists. FOXL2 mutation analyses could be performed successfully in 46 cases, 40 of which were positive for the c.402C>G mutation, confirming a diagnosis of aGCT. In the six cases negative for the c.402C>G mutation, one case was confirmed on review as FOXL2 wild‐type aGCT, whereas in the remaining five cases diagnoses other than aGCT were made. Conclusion In cases where a diagnosis of aGCT is a consideration and unequivocal diagnosis is not possible based on morphology and routine immunostains, FOXL2 mutation testing can help to confirm the diagnosis. It is particularly relevant for accurate subclassification within the group of sex cord–stromal tumours.